Does the presence of postmenopausal symptoms influence susceptibility to vertebral deformity? European Vertebral Osteoporosis Study (EVOS) Group. - Scoutellas, V; O'Neill, T; Lunt, M; Reeve, J; Silman, A (1999)
BACKGROUND: Previous reports suggest a possible increased risk of osteoporosis in those with postmenopausal symptoms. There are, however, no data from population samples, exploring the relationship between postmenopausal symptoms and vertebral osteoporosis. AIM: To determine if there is an association between self-reported postmenopausal symptoms and radiographic vertebral deformity. METHODS: Women aged 50 years and over were recruited from population registers in 30 European centres and invited to attend for an interviewer administered questionnaire and lateral thoracic and lumbar spine radiographs. The questionnaire sought information about aspects of lifestyle, personal, medical and gynaecological history, including postmenopausal symptoms: flushing, sleep disturbance and 'other' symptoms. Radiographs were taken according to a standard protocol and evaluated morphometrically. Vertebral deformity was defined according to the McCloskey-Kanis method. Bone mineral density data were obtained in a subsample of women at both the spine and femoral neck. RESULTS: A total of 4023 postmenopausal women, aged 50-64 years, were studied: 73% reported a history of flushing, 45% sleep disturbance and 23% 'other' symptoms, at or around their menopause. The prevalence of vertebral deformity was 8.2%. Those with postmenopausal symptoms were slightly younger and more likely to have ever taken hormone replacement therapy (HRT) than those without symptoms. After adjusting for potential confounders (age, centre, body mass index, cigarette smoking and HRT) there was no association between deformity and any of the postmenopausal symptoms: flushing (odds ratio (OR) 1.0; 95% confidence intervals (CI) 0.8, 1.3), sleep disturbance (OR 1.0; 95% CI 0.8, 1.2), 'other' symptoms (OR 0.9; 95% CI 0.7, 1.3). Amongst women who had ever taken HRT, however, those with vertebral deformity were more likely to report a history of flushing (OR 2.1; 95% CI 0.9,4.8). CONCLUSION: A history of postmenopausal symptoms per se does not appear to be associated with increased susceptibility to vertebral osteoporosis. However, women with more severe symptoms (as suggested by their use of HRT) may be at increased risk.